2000
DOI: 10.1097/00006324-200006000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors in Singapore and Xiamen, China—A Comparative Study in School Children Aged 6 to 7 Years

Abstract: The myopia rate in Singapore city was higher than in Xiamen city; the lowest rates were found in Xiamen countryside. As the Chinese population from all three sites is of similar genetic stock (predominantly from Southern China), it is postulated that the differences in myopia rates in these three localities may be related to environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 30 publications
7
47
2
Order By: Relevance
“…With one exception, multiple data available for any one country, including Australia [7,8], Denmark [13,14], Singapore [17,18], Taiwan [20], United Kingdom [21,22], and USA [23][24][25] show a rise with age. The exception is China [11,12], raising the question of whether anisometropia shows a significant prevalence amongst the very young [26], only to vanish with the development of binocular vision, when the magnitude of the dioptric disparity is small [4,24]. Note that premature children show a relatively high prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…With one exception, multiple data available for any one country, including Australia [7,8], Denmark [13,14], Singapore [17,18], Taiwan [20], United Kingdom [21,22], and USA [23][24][25] show a rise with age. The exception is China [11,12], raising the question of whether anisometropia shows a significant prevalence amongst the very young [26], only to vanish with the development of binocular vision, when the magnitude of the dioptric disparity is small [4,24]. Note that premature children show a relatively high prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a preliminary study conducted in Xiamen in 1998 have been reported elsewhere. 19 Informed consent was obtained from parents after the nature of the study was explained, and the conduct of the study followed the tenets of the Declaration of Helsinki. Approval was obtained from the ethics committee, Singapore National Eye Center, and the ethics committee, Xiamen Eye Institute.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The prevalence of this disorder in Asian countries varies from 50% in China to 84% in Taiwan and Hong Kong (14)(15)(16)(17)(18)(19). The comparison of the prevalence of refractive errors in Malay, Chinese, and Indian children in Malaysia and Singapore indicated that the prevalence of myopia was higher in children in Singapore from all the ethnic groups.…”
Section: Introductionmentioning
confidence: 99%